Determination of financial literacy and financial inclusion on the performance of MSMEs and financial resilience of MSMEs owners - Febriawan Ardi Nugroho; Hwihanus Hwihanus (Enrichment : Journal of Management, 2023)
This study aims to analyze the role of financial institutions in improving the performance of Micro, Small and Medium Enterprises (MSMEs). The role of financial institutions is urgently needed to develop Micro, Small and Medium Enterprises (MSMEs). However, conditions in the field still face many problems and difficulties for Micro, Small and Medium Enterprises (MSMEs) and make Micro, Small and Medium Enterprises (MSMEs) not develop so fast. According to the findings of the 2022 SNIK conducted by OJK, the financial literacy index of Indonesians is 49.68 percent in 2022, up from only 38.03 percent in 2019; meanwhile, the financial inclusion index this year reached 85.10 percent, up from 76.19 percent during the previous SNLIK period in 2019. These conditions made the researchers to attend, to see from the point of view of Micro, Small and Medium Enterprises (UMKM) and is expected to be able to overcome the problems and difficulties faced by Micro, Small and Medium Enterprises (UMKM). The study's findings reveal the impact of each factor, including financial literacy, financial inclusion, financial resilience, and micro, small, and medium-sized enterprise (MSME) performance.